2022
DOI: 10.3389/felec.2022.838472
|View full text |Cite
|
Sign up to set email alerts
|

Paper and Salt: Biodegradable NaCl-Based Humidity Sensors for Sustainable Electronics

Abstract: Flexible and thin-film humidity sensors are currently attracting the attention of the scientific community due to their portability and reduced size, which are highly useful traits for use in the Internet o Things (IoT) industry. Furthermore, in order to perform efficient and profitable mass production, it is necessary to develop a cost-effective and reproducible fabrication process and materials. Green fabrication methods and biodegradable materials would also minimize the environmental impact and create a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…The solution acted as a transmission medium, and currents from 1.3 to 1.9 A (15.6–22.8 W) were obtained. The conduction of NS 0.9% has been described to be of 1.45 S/m ( Falco et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The solution acted as a transmission medium, and currents from 1.3 to 1.9 A (15.6–22.8 W) were obtained. The conduction of NS 0.9% has been described to be of 1.45 S/m ( Falco et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…These sensors exhibit the best linearity in terms of the RH-impedance modulus, minimum hysteresis, and acceptable responses to variations in humidity. As a sensitive material [97,98], or as a component of a composite [95,100], paper can be also employed in impedance humidity sensors. However, it was found that almost all paperonly sensors become sensitive to H 2 O when the relative humidity is higher than 50-60%.…”
Section: Impedance Paper-based Humidity Sensorsmentioning
confidence: 99%
“…Some research studies found that it is necessary to functionalize paper to expand a range of relative humidity levels and improve the sensitivity of humidity sensors. In particular, to improve paper's conductivity, the treatment of paper with a solution of NaCl [97] or NaOH [98] was found to be highly powerful. According to Farrell et al [103], when alkali and cellulose are mixed in solution to form reactive EPTAC (epoxy propyl trimethylammonium chloride), trimethyl amine is emitted.…”
Section: Impedance Paper-based Humidity Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Paper is used as a microuidic substrate for the identication of various biomolecules and the examination of liquids. [23][24][25][26][27] In order to restrict the amount of uids that are dispersed on the paper substrate, hydrophobically patterned paper is utilised in the process of conducting targeted chemical analysis. [28][29][30] Furthermore, the amount of sample needed for this analysis is smaller in comparison to conventional chemical analysis.…”
Section: Introductionmentioning
confidence: 99%